Microscopic characterisation of spheroids / Zawiah Ahmad - Ahmad, Zawiah (2008)
The influence of microwave treatment on spheroid pore and surface characteristics against drug release profile was investigated. The spheroids were prepared by extrusion spheronization process followed by drying in hot air oven. Both blank and drug loaded spheroids were treated by microwave. The physical changes of spheroids were observed microscopically using a stereo microscope to observe the changes before and after spheroids subjecting to microwave treatment. Drug release profile was determined by performing drug dissolution test for both untreated and treated spheroids. Microwave treatment changed pore and surface characteristics of spheroids. However, an increase in drug dissolution of microwave treated spheroids did not necessary accompany by an increase in pore population of spheroids. Other factors such as drug-polymer interaction, polymer-polymer interaction, polymorphism and crystallinity of drugs, could have roles in drug dissolution.